Unconstitutional Usurpation of Power: An Evaluation of the Corporate Transparency Act’s Potential Demise Under National Small Business United v. Yellen - Matthew Hemmersmeier (Washington University Journal of Law and Policy, 2026)
The longstanding role of the judiciary has been to say what the law is and not what it should be. Nowhere is this axiom more illustrative than in National Small Business United v. Yellen. The National Small Business Association (NSBA) is a non-profit corporation tasked with representing and protecting the rights of small business owners as they navigate government regulation. Through the Corporate Transparency Act (CTA), Congress imposed disclosure requirements on corporations, limited liability companies, and other entities registered under state law, requiring them to disclose personal stakeholder information to the Treasury Department’s criminal enforcement branch. After exempting many large entities with millions in profits, these disclosure requirements primarily impacted small, family-owned businesses. Isaac Winkles was a small business owner who was impacted by the CTA’s hefty disclosure requirements. Had owners like Isaac Winkles failed to provide all information regarding their business’ beneficial ownership, they would personally face severe civil and criminal penalties. Deeming the CTA to be a clear overreach of Congress’ authority under Article I of the Constitution, the NSBA and Isaac Winkles sued the Treasury Department. The United States District Court for the Northern District of Alabama (District Court) determined that the CTA, as originally enacted, exceeded the constitutional limits imposed on Congress and did not have a sufficient connection between the statute and any enumerated powerof the legislative branch to be considered a necessary or proper use of such authority. This Comment examines the District Court’s decision to strike down the CTA as applied to NSBA and Isaac Winkles, understanding it to be an unconstitutional usurpation of federal power as outlined by the Constitution. By investigating the legislative history behind the CTA, this Comment seeks to lay a foundation for the various powers of Congress granted in Article I. With an analysis of Congress’ Article I powers, this Comment then evaluates the District Court’s judgment, finding it appropriate given core federalism principles and the policy impact on small business owners like Isaac Winkles. Specifically, in analyzing Congress’ foreign affairs, Commerce Clause, Taxing Clause, and Necessary and Proper Clause powers, this Comment reveals the congressional overreach displayed in the CTA, directly leading to the District Court’s holding. As noble as the CTA’s purpose may be in regulating and combatting financial crimes, the judiciary’s role should not permit Congress’ noble pursuits to contravene the Constitution’s limits. In taking the approach to say what the law is and not what it should be, this Comment argues that the District Court properly understood the CTA, as originally applied, to be an unconstitutional usurpation of power.
Keywords: #CorporateTransparencyAct; #SmallBusiness; #Federalism; #CommerceClause; #NSBAvYellen